2016
DOI: 10.4136/ambi-agua.1759
|View full text |Cite
|
Sign up to set email alerts
|

Life cycle assessment of four potable water treatment plants in northeastern Colombia

Abstract: There is currently great concern about the processes that directly or indirectly contribute to the potential for global warming, such as stratospheric ozone depletion or acidification. In this context, and provided that treated water is a basic public utility in urban centers around the world as well as in some rural areas, its impact on the environment is of great interest. Therefore, this study applied the environmental methodology of Life Cycle Assessment (LCA) to evaluate the environmental loads of four po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 22 publications
3
7
0
1
Order By: Relevance
“…The SimaPro ® software, faculty version, which has a large database and impact assessment methods, was used to build the LCI. This software has been widely applied by several researchers (e.g., Uche et al, 2015;Garfí et al, 2016;Rodriguez et al, 2016;Pokhrel et al, 2020;Rasul and Arutla, 2020;Trinh et al, 2020), as it allows creating a model of the studied system, inserting the inventory (manually or using databases), and calculating impacts using different life-cycle impact assessment methods.…”
Section: Life-cycle Assessmentmentioning
confidence: 99%
“…The SimaPro ® software, faculty version, which has a large database and impact assessment methods, was used to build the LCI. This software has been widely applied by several researchers (e.g., Uche et al, 2015;Garfí et al, 2016;Rodriguez et al, 2016;Pokhrel et al, 2020;Rasul and Arutla, 2020;Trinh et al, 2020), as it allows creating a model of the studied system, inserting the inventory (manually or using databases), and calculating impacts using different life-cycle impact assessment methods.…”
Section: Life-cycle Assessmentmentioning
confidence: 99%
“…Dalam penelitian tersebut, metode pengukuran indikator lingkungan menggunakan CML 2001. Metode tersebut hanya menghasilkan 6 indikator pengukuran [6]. Penelitian terkait siklus hidup pengolahan air khususnya air limbah juga pernah dilakukan di Cina.…”
Section: Pendahuluanunclassified
“…In assessing the lifecycle of several potable water treatment facilities in the northeast region of Colombia, Ortiz, Villamizar-Gallardo, and García (2016) concluded that, in order to be sustained in the long-term, many are in need of significant improvement or substantial adaptation to an alternative type of technology better suited to the operation, maintenance, management, and resource capacities of local communities. Quiroga (1996) believes that multi-stage filtration is a good example of such alternative technology.…”
Section: Areas Of Opportunitymentioning
confidence: 99%
“…In San Felipe, a small, central municipality, water was improved by incorporating treatment through multi-stage filtration -a mixture of gravel roughing and slow sand filtration -as part of a technology transfer project designed to improve the water distribution network plagued by leaks in taps, pipes, and toilets. Ortiz et al (2016) discuss the municipality of La Castilla, where the distribution system was planned and constructed without much community involvement, meaning that it was badly designed and constructed as a result. The authors strongly advocate for community participation at both the design and construction stage to guarantee ongoing success, arguing that 'it is well known that community participation in the entire project cycle is a determining factor for having a greater chance of ensuring a sustainable water supply project, especially in rural areas.…”
Section: Areas Of Opportunitymentioning
confidence: 99%